An experimental study on effect of inclination angle on the performance of a PCM-based flat-type heat sink. (25th February 2018) - Avci, Mete; Yazici, Mustafa Yusuf
Highlights: Effect of inclination angle on thermal performance of a PCM-based flat-type heat sink is investigated. An imaging technique is used to visualize the movement of melting interface. Inclination angle has a remarkable effect on the thermal performance in the range of 15–75°. The operating time is increased at least 5.5 times as the inclination angle increased from 0° to 90°. Abstract: An experimental study is carried out to investigate the effect of inclination angle on the thermal performance of a flat-type heat sink. Heat sinks without and with PCM are examined comparatively. The range of inclination angle from θ = 0° (vertical) to θ = 90° (horizontal) is considered. N-eicosane with a melting range of 35–37 °C is used as PCM. Temperatures are measured to characterize the heat transfer in air and PCM domains. In addition, an imaging technique is used to visualize the movement of melting interface. The results obtained show that the inclination angle has a remarkable effect on the thermal performance of the PCM-based heat sink while its effect is negligible for the one without PCM.